基于刚柔耦合建模的平行分度凸轮机构动力学分析 - 赵浩东; 曹艳科; 郭培全 (Jixie chuandong)
Dynamic modelling method of parallel indexing cam mechanism is presented based on multi-body system dynamics according to the analysis of mechanism feature.Rigid-flexible coupled dynamic model is established by means of ADAMS,Pro/E and ANSYS.Dynamic simulation is carried out,and according to the analysis result of simulation,the conclusion that cosine motion commonly used in engineering is unfit for using in high speed,heavy load and precision transmission cases is got.The effects of load inertia,input speed,and stroke angle on system output response are detailedly illustrated.